2018
DOI: 10.1017/s1744133117000548
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary physicians’ fees: a sustainable system?

Abstract: In Belgium and France, physicians can charge a supplementary fee on top of the tariff set by the mandatory basic health insurance scheme. In both countries, the supplementary fee system is under pressure because of financial sustainability concerns and a lack of added value for the patient. Expenditure on supplementary fees is increasing much faster than total health expenditure. So far, measures taken to curb this trend have not been successful. For certain categories of physicians, supplementary fees represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…One of the additional measures could be an introduction of copayments or of "supplementary fees" on top of the official tariffs set by the health insurance system (e.g. alike those in Belgium and France) [45]. Improvements in the health workforce system and its supply should also be considered.…”
Section: Policy Advocacymentioning
confidence: 99%
“…One of the additional measures could be an introduction of copayments or of "supplementary fees" on top of the official tariffs set by the health insurance system (e.g. alike those in Belgium and France) [45]. Improvements in the health workforce system and its supply should also be considered.…”
Section: Policy Advocacymentioning
confidence: 99%
“…In concrete terms, it is easiest to think of quality as the time a physician spends with a patient to conduct a procedure". This de…nition -which re ‡ects the healthcare situation in France -does not suggest a di¤erence in quality of medical care provided per se, rather substantial di¤erences in the non-medical dimensions of the service and patient-perceived quality of care (Calcoen and van de Ven, 2019). In particular, it has been shown that sector 2 specialists perform longer consultations (+4% in per-patient consultation time) than their sector 1 counterparts, all other things being equal (DREES, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Why then would anyone pay an out‐of‐pocket fee for a consultation in sector 2, when consulting a specialist in sector 1 is effectively free (except for the 1 euro copayment)? The differentiating factor is the quality of the service provided, defined broadly by Glazer and McGuire (1993) as: “any costly nonprice attribute of health care that affects patients' valuation, including dimensions of convenience, comfort, communication about medical conditions, and other factors… In concrete terms, it is easiest to think of quality as the time a physician spends with a patient to conduct a procedure.” This definition—which reflects the health care situation in France—does not suggest a difference in the quality of medical care provided per se, rather substantial differences in the nonmedical dimensions of the service (amenities) and patient‐perceived quality of care (Calcoen & Van de Ven, 2019). In particular, it has been shown that, all other things being equal, sector 2 specialists perform longer consultations than their sector 1 counterparts; the spread can be as high as 5 min (15%) in psychiatry and cardiology (DREES, 2006; Guyon, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, although the government offers health-care subsidies to local citizens, no evidence has been presented on whether service fees provide a better quality of care to patients (Calcoen and Van de Ven, 2019). The relationship between health-care quality and price and payment of health-care procedures was under investigation (Chen and Miraldo, 2022).…”
Section: Introductionmentioning
confidence: 99%